Analysis of Cinema Therapy Technique for Increasing Self-Confidence in Adolescent Victims of Prejudicial Bullying - Padillah, Raup; Hidayah, Nur; Setyosari, Punaji; Hambali, IM; Indreswari, Henny (Universitas Mercu Buana Yogyakarta, 2024)
With the most bullying cases, Indonesia takes the top spot. With 84% of the vote, Indonesia holds the top spot. More than Vietnam and Nepal combined, this figure is higher. Pakistan came in third with 43%, and Cambodia came in second with 73%. According to KPAI data, there would be 226 instances of bullying in addition to physical and psychological abuse in 2022. In this are figures. is quite big, and all the parties concerned need to pay attention to it. As a result of bullying, victims often have low self-confidence, according to some research findings. Several studies have found that adolescents frequently struggle with self-confidence issues. How about making one of those initiatives to help victims of prejudiced bullying deal with their lack of confidence? is to create methods for self-reflection via movie therapy. The finest alternative to traditional therapy is film therapy.